2008
DOI: 10.1007/s00431-008-0719-9
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of erythrocyte membrane lipids in healthy subjects from birth to young adulthood

Abstract: The fatty acid composition of erythrocyte membrane lipids may better reflect the fatty acid status of the organism than the fatty acid composition of plasma lipids. The present study aimed to provide normal values for erythrocyte fatty acid composition in a sizeable group of healthy subjects throughout the paediatric age group. The fatty acid composition of erythrocyte membrane phosphatidylcholine (PC) and phosphatidylethanolamine (PE) lipids was determined by high-resolution capillary gas chromatography in 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 22 publications
4
17
1
Order By: Relevance
“…We recently compared fatty acid compositional data obtained from erythrocyte membrane lipids in 17 newborns with those from 97 infants investigated at the median age of 6 mo (39). Median TFA values decreased significantly between the 2 periods investigated, from 0.60% to 0.43% in phosphatidylcholine lipids and from 0.66% to 0.30% in phosphatidylethanolamine lipids (39). The significant decrease in erythrocyte membrane TFA values from birth to the age of 6 mo appears to run in parallel with the significant decrease in TFAs in HM by the age of 6 mo seen in another study (15).…”
Section: Tfa Exposure Of the Fetus And Infantmentioning
confidence: 83%
“…We recently compared fatty acid compositional data obtained from erythrocyte membrane lipids in 17 newborns with those from 97 infants investigated at the median age of 6 mo (39). Median TFA values decreased significantly between the 2 periods investigated, from 0.60% to 0.43% in phosphatidylcholine lipids and from 0.66% to 0.30% in phosphatidylethanolamine lipids (39). The significant decrease in erythrocyte membrane TFA values from birth to the age of 6 mo appears to run in parallel with the significant decrease in TFAs in HM by the age of 6 mo seen in another study (15).…”
Section: Tfa Exposure Of the Fetus And Infantmentioning
confidence: 83%
“…Whereas national data on the blood FA composition of young children stem mainly from small and a few large study populations, 27, 28, 29 international data from unselected populations are missing. Therefore, we aim to establish reference values for 3–8-year-old European children.…”
Section: Introductionmentioning
confidence: 99%
“…All classes of fatty acids are found in erythrocytes [18] including both n-3 and n-6 LCPUFA. As shown by Jakobik et al [19] and Sun et al [36], the fatty acid composition of erythrocyte membrane lipids may better reflect the fatty acid status of an organism than the fatty acid composition of plasma lipids. Studies have also confirmed that erythrocyte fatty acids are nutritional biomarkers that accurately reflect dietary intakes of specific fatty acids consumed over the past few months and over time in both adults and children [16,17,36].…”
Section: Discussionmentioning
confidence: 95%
“…However, only a few studies have described erythrocyte fatty acid composition in children and adults. Many of these studies considered erythrocyte fatty acid data from individuals living in high-income countries [18,19,21,22] or those with medical conditions [23][24][25], and some studies have only small sample sizes [20].…”
Section: Introductionmentioning
confidence: 99%